Discovery of Selective SIRT2 Inhibitors as Therapeutic Agents in B-Cell Lymphoma and Other Malignancies - Sarwat Chowdhury; Smitha Sripathy; Alyssa A. Webster; Angela Park; Uyen Lao; Joanne H. Hsu; Taylor Loe; Antonio Bedalov; Julian A. Simon (Molecules, 2020)
Genetic ablation as well as pharmacological inhibition of sirtuin 2 (SIRT2), an NAD+-dependent protein deacylase, have therapeutic effects in various cancers and neurodegenerative diseases. Previously, we described the discovery of a dual SIRT1/SIRT2 inhibitor called cambinol (IC50 56 and 59 µM, respectively), which showed cytotoxic activity against cancer cells in vitro and a marked anti-proliferative effect in a Burkitt lymphoma mouse xenograft model. A number of recent studies have shown a protective effect of SIRT1 and SIRT3 in neurodegenerative and metabolic diseases as well as in certain cancers prompting us to initiate a medicinal chemistry effort to develop cambinol-based SIRT2-specific inhibitors devoid of SIRT1 or SIRT3 modulating activity. Here we describe potent cambinol-based SIRT2 inhibitors, several of which show potency of ~600 nM with >300 to >800-fold selectivity over SIRT1 and 3, respectively. In vitro, these inhibitors are found to be toxic to lymphoma and epithelial cancer cell lines. In particular, compounds 55 (IC50 SIRT2 0.25 µM and <25% inhibition at 50 µM against SIRT1 and SIRT3) and 56 (IC50 SIRT2 0.78 µM and <25% inhibition at 50 µM against SIRT1 and SIRT3) showed apoptotic as well as strong anti-proliferative properties against B-cell lymphoma cells.